The seismic behaviour of precast concrete interior joints with different connection methods in assembled monolithic subway station. (1st April 2021) - Liu, Hongtao; Wang, Zhenyu; Du, Xiuli; Shen, Geoffrey Q.P.
Highlights: Seismic performance of precast joint was compared with cast-in-place joint. A new cross-lapping connection for concrete laminated slabs was introduced. The elastic–plastic boundary which was used to evaluate precast structures was explored. An effective range for thickness ratio of upper layer (cast-in-place concrete) and lower layer (precast concrete) was proposed. Abstract: The study investigated the performance of a specific full-scale precast concrete interior joint using many connected methods (e.g. grouted sleeves, anchorage arrangements, corbels) in the core region of joint, whilst a monolithic cast-in-place concrete specimen served as a control. The important indexes in terms of failure mode, hysteretic behavior, strength, deformation performance, and stiffness degradation were investigated under low-reversed cyclic loading. The new cross-lapping connection of concrete slab was presented and the position of the interface between two layers of lamination slab was optimized. The experimental and analysis results indicated that, (1) the precast concrete specimens were capable of matching peaking strength and deformation performance of the monolithic cast-in-place joint, while the displacement ductility and failure modes of two joints were different; (2) the elastic–plastic boundary of 1/550 which was used to evaluate precast structures should be carefully selected in the design; (3) an effective range for the thickness ratio of upper layer (post-pouring concrete) and lower layer (precast concrete) was presented; (4) a new cross-lapping connection for bend-up reinforcement at the ends of the semi-precast slab was performed for another optional method.